Controversial Nomenclature of Ayurvedic drugs: Challenges for Scientists - Dobriyal, Rajendra M; Ananthanarayana, DB (Pharmacognosy Reviews)
Ayurveda, the traditional system of medicine in India is understood to have evolved many thousands years back. Ayurvedic medicines are made using materials of plant, mineral, metal and animal origin. However, plants constitute about 80 percent of the raw materials used in Ayurvedic recipes. Though the classical text books of Ayurveda cumulatively document about 1500 plants, about 600 plants are commonly used for manufacturing medicines currently in India. Many of plant drugs documented in Ayurvedic textbooks have a controversy on their accurate botanical linkages. Since plants and plant drugs in Ayurveda were designated Sanskrit names, often based on the “doctrine of signature”, morphological appearance, properties and action, the interpretation of these names during the later period of time led to acceptance of more than one botanical species for one plant drug. An attempt has been made here to map the extent of this controversy as reflected in one of the most referred text books of Ayurveda, Bhavprakash Nighantu. We report here the controversies due to lack of precise nomenclature of plant drugs in Ayurveda and its impact on regulatory scenario. Aspects related to adulteration and substitutions are not covered.
Keywords: Ayurveda; nomenclature; substitution; adulteration; controversial drugs